2009
DOI: 10.1148/radiol.2511080400
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Patients with Cirrhosis: Qualitative Comparison of Gadobenate Dimeglumine–enhanced MR Imaging and Multiphasic 64-Section CT

Abstract: The combined interpretation of dynamic and hepatobiliary phase MR images improves diagnostic accuracy of gadobenate dimeglumine-enhanced MR imaging for the detection of HCC compared with either dynamic MR or multiphasic multidetector CT images alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 30 publications
7
54
0
Order By: Relevance
“…20,22 Previous studies showed improved diagnostic sensitivity/ PPV by adding HP images to dynamic MR imaging or by comparing them with CECT. 7,8,20,[23][24][25] Our results agreed with those of the previous studies. Using hypointensity as a major feature, we can more effectively categorize a hypovascular HCC of at least grade LR3.…”
Section: Discussionsupporting
confidence: 93%
“…20,22 Previous studies showed improved diagnostic sensitivity/ PPV by adding HP images to dynamic MR imaging or by comparing them with CECT. 7,8,20,[23][24][25] Our results agreed with those of the previous studies. Using hypointensity as a major feature, we can more effectively categorize a hypovascular HCC of at least grade LR3.…”
Section: Discussionsupporting
confidence: 93%
“…Third, to minimize false categorization in evaluating responses, 2 independent radiologists interpreted radiologic responses and final classifications made by consensus between them were ultimately adopted. In our study, the high levels of concordance between the 2 readers were observed compared with other literatures (22)(23)(24). This is most likely because radiologists assessed responses using the given number of target lesions (i.e., up to 1 target, up to 2 targets, and so on) according to the main concept of this study.…”
Section: Discussionsupporting
confidence: 50%
“…Marin et al [41] demonstrated that EOB-MRI with the combined interpretation of dynamic triple-phase MRI and HBP-MRI significantly improved the sensitivity of HCC detection (72%) compared with either dynamic MRI (63%) or MDCT images alone (61%; p = 0.008 and 0.001, respectively). This result was even more valuable for lesions 1-2 cm in diameter.…”
Section: European Literaturementioning
confidence: 99%
“…Unfortunately, the Western guidelines have not advanced in the same way as the above-mentioned European literature [41,42,43,44,45]; neither the AASLD [7,55] nor EASL-EORTC guidelines [6,8] have included EOB-MRI in the diagnostic flowchart and in the follow-up, and they also do not acknowledge the diagnostic superiority of dynamic MRI over MDCT, which has been widely demonstrated [41,42]. On the other hand, the Italian Association for the Study of the Liver recommendations [56] recognizes these topics and introduces some statements, such as ‘multiphasic MRI with hepatocyte-specific contrast medium may provide additional clues to the diagnosis of HCC and is superior to CT for intrahepatic staging of the tumor' and ‘intrahepatic staging of HCC should be assessed by MRI whenever the patient appears to be a potential candidate for surgical or ablative treatment, as this radiological technique is more accurate than CT'.…”
Section: East-west Differencesmentioning
confidence: 99%